TiO2-SO42- Catalyzed Synthesis and Antimicrobial Activity / Molecular Docking Studies of β-Indolylnitroalkanes - Santhisudha, Sarva; Harinath Jayaprakash, Soora; Mohan, Gundluru; Nanda Kumar, Yellapu; Suganthi, Vaithiyanathan; Mohanasrinivasan, Vaithiyalingam; Suresh Reddy, Cirandur (Combinatorial Chemistry & High Throughput Screening, 2016)
Michael addition of indole derivatives with various substituted nitrostyrenes to yield β- indolylnitroalkanes is accomplished effectively under solvent free conditions using TiO2-SO42- as efficient catalyst at 60 º C. All the synthesized compounds were screened for their antibacterial activity through in silico and in vitro methods. The molecular docking studies against FabH enzyme, a potential drug target of bacterial fatty acid biosynthetic pathway indicated the scope of developing them a new class of antimicrobial agents. Among the title compounds, 5h exhibited the highest dock score and the highest antibacterial activity when compared with other compounds and the standard drug Ampicillin. In addition, the compounds 5d, 5e, 5g, 5h, 5i, 5j and 5l showed significant inhibitory activity at different dose concentrations under in vitro conditions against the specified bacterial strains thus qualifying for further clinical evaluation so that they can be used as effective anti-bacterial agents.
Keywords: β-indolylnitroalkanes